Celiac disease in children with type 1 diabetes varies around the world: An international, cross‐sectional study of 57 375 patients from the SWEET registry. Issue 6 (30th November 2020) - Taczanowska, Anna; Schwandt, Anke; Amed, Shazhan; Tóth‐Heyn, Péter; Kanaka‐Gantenbein, Christina; Volsky, Sari Krepel; Svensson, Jannet; Szypowska, Agnieszka
Abstract: Background: Children with type 1 diabetes (T1D) are at much higher risk of developing celiac disease (CD) than the general population. The aim of the study was to assess the prevalence and differences in clinical presentation of CD in T1D in different regions of the world. Methods: This study is based on the Better control in Pediatric and Adolescent diabeteS : W orking to crE ate cE nT ers of Reference (SWEET) database. There were 57 375 patients included in the study, aged ≤18 years from 54 SWEET centers. Only centers with screening for celiac disease were included. Regression models adjusted for age, diabetes duration, and gender and a fixed effect in the models for region was used. Diabetes duration, age at diabetes onset, and sex were presented as unadjusted results. Results: CD was present in 2652 subjects (4.5%), with different prevalence among regions: from 1.9% in Asia/Middle East to 6.9% in Australia/New Zealand. CD was observed more often among females. Comparing children with and without CD, characteristics for those with CD were younger age at diabetes onset (6.3 [3.3; 9.8] vs 8.1 [4.6; 11.3], P  < 0.001) and had longer diabetes duration (6.4 [3.6; 9.8] vs 4.8 [2.1; 8.2], P  < 0.001). Further, they had lower glycosylated hemoglobin (HbA1c) in Europe and North America/Canada; lower body mass index (BMI)‐SD score (BMI‐SDS) in southern Europe, North America, and Canada; In most regions daily insulin dose was lower, height‐SDS was lower, and the percentage of insulin pump users was higher in children with T1D and CD. Conclusions: The prevalence and the anthropometric and metabolic consequences of CD in children with T1D differ around the world. Abstract : Highlights There are worldwide differences in the frequency of CD in children with T1D with higher prevalence in girls and those with young onset. Differences in anthropometric outcomes in children with T1D and CD highlights the importance of close follow‐up of growth and antibodies in these children. In many regions, children with CD and T1D are more likely to use modern technologies compared to non‐CD subjects. Diabetes control in children with CD and T1D varies between regions and needs improvement. 摘要: 背景: 1型糖尿病(T1D)儿童患乳糜泻(CD)的风险比普通人群高得多。该研究旨在评估CD在世界不同地区T1D中的患病率和临床表现的差异。 方法: 这项研究基于"致力于更好控制儿童和青少年糖尿病:注册参考中心" (SWEET)数据库。这项研究包括了来自54个中心的57375名年龄≤ 18岁的患者。有乳糜泻筛查的中心被纳入其中。回归模型根据年龄、糖尿病病程和性别进行了校正，模型中对地区的影响是固定的。糖尿病病程、发病年龄和性别展示的是未校正的结果。 结果: 2652名受试者(4.5%)存在CD，不同地区的患病率不同:从亚洲/中东的1.9%到澳大利亚/新西兰的6.9%。CD多见于女性。CD组与非CD组相比，发病年龄小(6.3 [3.3; 9.8] vs 8.1 岁[4.6; 11.3]，P<0.001)，病程长(6.4 [3.6; 9.8] vs 4.8 [2.1；8.2]年，P<0.001)。此外，此外，欧洲和北美/加拿大的糖化血红蛋白(HbA1c)较低，南欧、北美和加拿大的体重指数(BMI)SD评分(BMI‐SDS)较低，在大多数地区T1D和CD儿童的胰岛素每日剂量较低，身高‐SDS较低，使用胰岛素泵的比例较高。 结论: CD在T1D儿童中的患病率、人口学和代谢指标在世界各地都不同。